The Abundance of Kelp Is Modified by the Combined Impact of Depth, Waves and Currents - Bekkby, Trine; Smit, Cecilie; Gundersen, Hege; Rinde, Eli; Steen, Henning; Tveiten, Lise; Gitmark, Janne K.; Fredriksen, Stein; Albretsen, Jon; Christie, Hartvig (Frontiers in Marine Science, 2019)
This study analyses the combined impact of two types of ocean water flow, wave exposure and ocean currents, on kelp Laminaria hyperborea abundance, taking other environmental co-variables into account. The dataset covers many ecoregions along the NE Atlantic (Norwegian) coast, including both the Skagerrak, the North Sea and the Norwegian Sea, from 58°N to 66°N. Our results show that the abundance of kelp is modified by the combined impact of depth, waves and currents and that high kelp abundance is found mainly in relatively shallow and flat terrain in wave exposed and low current areas. The analyses reveal significant interactions between wave exposure and both depth and ocean currents, implying depth-specific effects of wave exposure and wave-specific effects of current speed. The somewhat surprising influence of temperature is discussed. The ecological function and ecosystem services of kelp forests are related to kelp abundance. Knowledge on how abundances vary with environmental variables is therefore highly relevant for developing large scale models to quantify and visualise (on maps) macroalgae biomass and ecosystem services, such as wave dampening, carbon storage and raw material provisioning.